Marēfī-yē sangnēgārēhayē noyāftē ba neghoshē heyvānī dar barēssīyē bāstānshēnākhtī-yē manteghē-ī-yē Fārs-ē Jonubī (Dashtē Bēyram) = [Introduction to Newly Discovered Petroglyphs with Animal Motifs During an Archaeological Survey in Southern Regions of Fars (the Beyram Plain)] - SARKHOSH, Ahmad; NAZARI, Samer; SHA'RBAF, Marzieh (Historia i Świat, 2015)
The rock art has particular position in anthropological and archaeological studies. Analysis of these motifs plays a significant role in understanding culture, beliefs, social relations and other aspects of daily life. Creation of petroglyphs has a long history in Iran and are widespread in most parts of the country. The area of study in this essay is Beyram plain which is located in Larestan city in the southern part of Fars province. During archaeological systematic survey in this area, some petroglyphs with various animal motifs were detected and recorded, that can be considered as a part of art and memorials of residents in this settlements. The relative chronology of these motifs is based on analogy and comparative studies with obtained samples from adjacent areas. This research has been performed through both field study and library method. It used the descriptive-analytical methods in order to present, describe, design and compare the newly discovered petroglyphs at Beyram plain. In order to have a detailed analysis of the motifs, ethnographic studies and talking with shepherds and natives were done. And based on these studies, a possible function will be suggested for these kinds of motifs.